Psychiatric and social characterisation of suicide attempts treated at a children's clinic, 2003-2005. (2007)
OBJECTIVE: Psychiatrically and socially characterising suicide attempts treated at a children's clinic in Bogota, 2003-2005.METHODS: A retrospective series of 96 cases aged 11-18, using univariate and bivariate statistical analysis.RESULTS: 81,4 % of the cases were female. Mean age was 15,3 years and 70,9 % were aged 16 or younger. Low family income was found in 63,1 %. Poisoning was the suicide method in 96,9 % cases. Ambulatory care for two months or less was continued in 38 % cases. Only 13,2 % required anti-depressive or mood-modulator medicine. 87,9 % suffered family or scholastic stress. 83,5 % had a problematic relationship with parents and in 72,3 % of cases the parents had a conflictive relationship. 46,5 % were first-born children. Forty abuse situations were found. 27,2 % had attempted suicide previously. Adjustment disorders, family dysfunction and mood disorders were the main psychiatric diagnostics. 37,6 % had scholastic problems, suffered academic failure or had conflict with their teachers. Males were associated with aggressiveness, substance use, academic failure or romantic loss and females were associated with predominant anxiety and physical abuse.DISCUSSION: Being young, the overrepresentation of females and suffering scholastic and family conflict were noteworthy. Gender association with socio-cultural, behavioural and emotional profile is also worth noting. Socio-family and scholastic conflict is frequent in youth people's suicide attempts. The child-youth suicide problem must be made socially visible to prevent it.